Determinants of Consumer Behavior on Social Media: An MBKM Student Activity at UIGM Supporting AKWET Pempek SMEs - Maulana, Fakhrezi; Hertati, Lesi; Asharie, Asmawati (International Journal of Social Science and Community Service, 2023)
Pempek Akwet is a food sector MSME located in 26 Ilir, Palembang. which has been around for approximately 7 to 8 years. As the name implies, Pempek Akwet provides a variety of food products such as pempek, tekwan, gado-gado and others. The purpose of this research was to find out the data method of consumer grouping and the use of social media. The method used is a qualitative method by interviewing the owner of Pempek Akwet. The results of this research are useful for pempek Akwet in understanding consumer behavior so that they can develop appropriate marketing content on social media owned by pempek Akwet. By using organic marketing techniques through social media, specifically Instagram and Whatsapp, Pempek Akwet managed to increase turnover and sales by reaching a wider market and increasing brand awareness in Palembang. The use of social media features such as likes, comments, engagement, and insights has helped Pempek Akwet analyze consumer data and expand content reach, making this research a valuable reference for MSMEs looking to leverage digital marketing for their business growth.